Fruiting-body formation and myxospore differentiation and germination in Mxyococcus xanthus viewed by scanning electron microscopy. - Shimkets, L (1975)
Streaming cells, fruiting bodies, and single cells undergoing myxospore differentiation and germination were examined in the FB strain of Myxococcus xanthus by scanning electron microscopy. Myxospores differentiated in fruiting bodies differed in size, in kinetics of germination, in the fate of the myxospore capsule, and in the external structure of the walls of newly emerged cells when compared with myxospores differentiated in liquid medium after glycerol induction. Vegetative cells outgrowing from glycerol-induced myxospores were regularly pleomorphic, a condition that persisted through the first cell division.